Apologising for the study of religion - no way! - Jensen, Tim 1950- (2017)
An initial apology to religious insiders in the opening of Hughes' book got this review - of the book and of tensions in public and academic discourse about Islam and the study thereof - started. The book, after the strange initial apology, becomes a highly valuable introduction to a study-of-religion approach to Islam, incorporating both insider and outsider perspectives, including primary sources and critical analyses, and describing the multitude of ‘Muslim identities’ and responses to so-called modernity. Desiderata: a more classical comparative approach to ritual and more nuance around its discussion of women and jihad. Returning to 'apologetics', the review renders a recent Danish debate suggesting scholars of Islam should investigate and expose Islam rather than provide a nuanced and qualified picture in accordance with empirical scientific principles. An example of public ignorance over the role of the scholar of religion, - and yet another example of the necessity of approaching Islam as any other religion, i.e. from a comparative, historical and critical-analytical point of view. Though the book (rightly) suggests that the academic study of religions is more novelty than norm, the reviewer sees no reason, whatsoever, for apologizing for study-of-religion principles and approaches to religion, Islam included.
Keywords: academic study of religion; insider-outsider perspectives; Islamophobia; method and theory; study of Islam; Rezension